A computational study of acidic Ionic Liquids for cellobiose hydrolysis in ionic liquids - Nel, Jessica Lisé (Department of Chemistry, 2020)
The current environmental situation, with respect to global warming and the ever– approaching depletion of fossil fuel sources, places significance on the development of green fuel and platform chemical production methods. In this context, processes that utilise biomass sources as feedstock, are of great interest. Cellulose, which is the most abundant biopolymer in nature, is a renewable low–cost carbon resource derived from harvest residues and sources like wood and straw. Glucose generation from cellulose requires a saccharide conversion, whereby the β-(1,4)-glycosidic bond linkages in the cellobiose polymer repeating units are cleaved. Problems arise in the hydrolysis of cellulose as experimental and theoretical studies have shown cellulose to have very low solubility in water and most other general molecular solvents. This results in the use of harsh pretreatments at high temperatures and pressures to extract cellulose from lignocellulosic material and strong acids catalysts (pKa < −3.2). Room temperature ionic liquids (RTILs) provide potentially environmentally friendly alternative. It has been shown that ILs can dissolve cellulose under relatively benign conditions and can possibly be adapted into a one-pot-like process of hydrolysis using acid-functionalised IL catalysts. This dissertation investigated the effect of various ionic liquids on the thermodynamics of cellobiose acid hydrolysis, as both a catalyst and as a solvent, using computational means. An appropriate thermodynamic cycle protocol, a DLPNO-CCSD(T)/ccpVTZ//TPSS/def2-TZVP [M05-2X/6-31+G** (SMD)] proton exchange cycle, was established through benchmarking for the prediction of Brønsted acid-functionalised ionic liquid pKa values in ionic liquids. The sulfonyl-functionalised acidic IL was shown to be the most acidic IL resulting in a lower protonation free energy. Solvation in ionic liquids resulted in higher protonation and barrier height free energies relative to solvation in water. The current environmental situation, with respect to global warming and the ever– approaching depletion of fossil fuel sources, places significance on the development of green fuel and platform chemical production methods. In this context, processes that utilise biomass sources as feedstock, are of great interest. Cellulose, which is the most abundant biopolymer in nature, is a renewable low–cost carbon resource derived from harvest residues and sources like wood and straw. Glucose generation from cellulose requires a saccharide conversion, whereby the β-(1,4)-glycosidic bond linkages in the cellobiose polymer repeating units are cleaved. Problems arise in the hydrolysis of cellulose as experimental and theoretical studies have shown cellulose to have very low solubility in water and most other general molecular solvents. This results in the use of harsh pretreatments at high temperatures and pressures to extract cellulose from lignocellulosic material and strong acids catalysts (pKa < −3.2). Room temperature ionic liquids (RTILs) provide potentially environmentally friendly alternative. It has been shown that ILs can dissolve cellulose under relatively benign conditions and can possibly be adapted into a one-pot-like process of hydrolysis using acid-functionalised IL catalysts. This dissertation investigated the effect of various ionic liquids on the thermodynamics of cellobiose acid hydrolysis, as both a catalyst and as a solvent, using computational means. An appropriate thermodynamic cycle protocol, a DLPNO-CCSD(T)/ccpVTZ//TPSS/def2-TZVP [M05-2X/6-31+G** (SMD)] proton exchange cycle, was established through benchmarking for the prediction of Brønsted acid-functionalised ionic liquid pKa values in ionic liquids. The sulfonyl-functionalised acidic IL was shown to be the most acidic IL resulting in a lower protonation free energy. Solvation in ionic liquids resulted in higher protonation and barrier height free energies relative to solvation in water.